2014
DOI: 10.1021/nl501077m
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Electronic Structure in Bilayer Molybdenum Disulfide via Interlayer Twist

Abstract: Molybdenum disulfide bilayers with well-defined interlayer twist angle were constructed by stacking single-crystal monolayers. Varying interlayer twist angle results in strong tuning of the indirect optical transition energy and second-harmonic generation and weak tuning of direct optical transition energies and Raman mode frequencies. Electronic structure calculations show the interlayer separation changes with twist due to repulsion between sulfur atoms, resulting in shifts of the indirect optical transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

42
322
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(368 citation statements)
references
References 46 publications
42
322
4
Order By: Relevance
“…This observation agrees with the density functional theory (DFT) calculation findings of He et al 9 in terms of the general trend but being different in value (0.06 eV from our PL study versus 0.14 eV from DFT calculations). Previous experimental results 19,21 did not address the difference between the I peak positions of AA 0 and AB stacked bilayer MoS 2 . In addition, the I/A peak intensity ratio in PL spectra obtained on a Au pyramid region is higher than that in the previous experiment results obtained on SiO 2 /Si substrates.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…This observation agrees with the density functional theory (DFT) calculation findings of He et al 9 in terms of the general trend but being different in value (0.06 eV from our PL study versus 0.14 eV from DFT calculations). Previous experimental results 19,21 did not address the difference between the I peak positions of AA 0 and AB stacked bilayer MoS 2 . In addition, the I/A peak intensity ratio in PL spectra obtained on a Au pyramid region is higher than that in the previous experiment results obtained on SiO 2 /Si substrates.…”
Section: Resultsmentioning
confidence: 88%
“…In addition, the I/A peak intensity ratio in PL spectra obtained on a Au pyramid region is higher than that in the previous experiment results obtained on SiO 2 /Si substrates. 19,21 The emergence of the indirect band gap results from the interlayer electronic coupling. In the bilayer MoS 2 band structure, the doubly degenerate valence band splits into more branches near the Γ point, and the upper branch reaches an energy value higher than the valence band at the K point in monolayer MoS 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that our results show that the A' 1 and E' peak energies of MoS2 do not seem to depend on the stacking angle between the two layers as shown in Figure S4, which is different from the recent studies on Raman spectra of bilayer MoS2 which shows twisting angle dependence. 46,47 This could be reasoned since the homo-bilayer might exhibit stronger interlayer coupling due to the same lattice constant for two layers (better matching between top and bottom layers).…”
Section: Resultsmentioning
confidence: 99%
“…Theoretical calculations have predicted that the stacking sequence in bi-layer MoS 2 plays an important role in its electronic band structure [14]. Experimental studies have found that the relative rotation angle in bi-layer MoS 2 significantly modifies the direct/indirect band gap and interlayer coupling [15,16]. The recently observed spin/valley polarization in symmetry-breaking 3R phase bulk MoS 2 (another commonly observed phase of bulk MoS 2 ) further elucidates the key role of stacking sequences (or crystal structure) in the properties of layered MoS 2 [17].…”
Section: Introductionmentioning
confidence: 99%